Intracellular spermine decreases open probability of N-methyl-D-aspartate receptor channels - Turecek, R; Vlcek, K; Petrovic, M; Horak, M; Vlachova, V; Vyklicky, L (Neuroscience, 2004)
Spermine and related polyamines have been shown to be endogenous regulators of several ion channel types including ionotropic glutamate receptors. The effect of spermine on N-methyl-d-aspartate (NMDA) receptors in cultured rat hippocampal neurons was studied using single-channel and whole-cell patch clamp recordings. Intracellular spermine resulted in the dose-dependent inhibition of NMDA-induced responses. Spermine reversibly inhibited the single NMDA receptor channel activity in inside-out patches suggesting a membrane-delimited mechanism of action. Open probability of NMDA receptor channels was decreased in a dose-dependent manner. Mechanism of spermine-induced inhibition of NMDA receptor was different from that of intracellular Ca(2+)-induced NMDA receptor inactivation. Both pharmacological studies and single channel analysis indicate that in contrast to the effect of extracellular spermine the intracellular spermine effect is not dependent on the NMDA receptor subunit composition. We propose that intracellular spermine has a direct inhibitory effect on NMDA receptors that is different from calcium-induced NMDA receptor inactivation and spermine-induced voltage-dependent inhibition of AMPA/kainate receptors. Spermine-induced tonic change in the open probability of NMDA receptor channels may play a role in mechanisms underlying short-term changes in the synaptic efficacy.
Keywords: Neurons; kultivované buňky; receptory N-methyl-D-aspartátu; Dose-Response Relationship, Drug; Electrophysiology; metoda terčíkového zámku; vztah mezi dávkou a účinkem léčiva; Rats; Animals, Newborn; hipokampus; elektrofyziologie; Receptors, N-Methyl-D-Aspartate; novorozená zvířata; Patch-Clamp Techniques; krysa rodu Rattus; Cells, Cultured; Intracellular Fluid; spermin; zvířata; neurony; intracelulární tekutina; Spermine; Hippocampus; Animals